IMPLEMENTASI PRIVATE CLOUD STORAGE MENGGUNAKAN RASPBERRY PI - Putra, Ricky Armidha (Jurnal Pengembangan Rekayasa dan Teknologi, 2021)
Cloud storage is a cloud computing model that stores data on a server that is accessed via the internet. Cloud storage is an option for storing data. The existing cloud storage service providers provide services at a fairly high price and cannot be configured according to the wishes of the user. Therefore, the author plans to implement a private cloud that uses a raspberry pi as a server for file management and Nextcloud as an interface. Nextcloud is an application that is very suitable for running cloud storage services. Nextcloud can share files with other users and share via a link via the web. To run cloud storage, users can access the server address with an intermediary web browser.The research method used in this research is Research and Development. Hardware test results obtained if used by more than 5 devices simultaneously will result in Requested Timed Out (RTO) on the Nextcloud page, in the future you can replace a better micro SD with fast data read/write access speed.